Positive electrode for lithium ion secondary battery and method for manufacturing the same
By employing a first conductive material to close the through holes and a second conductive material to form a conductive path in hollow-structured positive electrode active material particles, the electronic resistance is suppressed, improving the conductivity and performance of lithium ion secondary batteries.
Patent Information
- Application Number
- JP2023097182
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-13
- Publication Date
- 2024-12-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The use of conductive materials with diameters smaller than the through holes in hollow-structured positive electrode active material particles can lead to a reduction in the amount of conductive material outside the shell, resulting in increased electronic resistance due to a decrease in conductive paths.
A method involving the use of a first conductive material with a larger diameter than the through holes to close them, combined with a second conductive material with a smaller diameter to form a conductive path outside the shell, ensuring effective conductivity.
This approach effectively suppresses the increase in electronic resistance by forming a good conductive path, maintaining the integrity of the conductive network and enhancing the performance of the lithium ion secondary battery.
Smart Images

Figure 2024178780000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a positive electrode for a lithium ion secondary battery and a method for producing a positive electrode for a lithium ion secondary battery. [Background technology]
[0002] Secondary batteries are widely used as so-called portable power sources for personal computers, mobile terminals, etc., and as power sources for driving vehicles. In particular, lithium-ion secondary batteries, which are lightweight and can obtain high energy density, are suitably used as high-output power sources for driving vehicles such as electric vehicles, hybrid vehicles, and plug-in hybrid vehicles. Lithium-ion secondary batteries are secondary batteries that can be charged and discharged by the movement of lithium ions in an electrolyte between positive and negative electrodes that contain an active material that absorbs and releases lithium ions.
[0003] An active material suitable for use in a positive electrode of a lithium ion secondary battery may have low electronic conductivity. Therefore, when manufacturing a positive electrode, it is desirable to suppress an increase in electronic resistance of the positive electrode caused by using an active material with low electronic conductivity by mixing the active material with a conductive material such as a conductive carbon material.
[0004] Patent Document 1 discloses a method for producing a composite slurry containing an active material, a polyvinylidene fluoride resin, a good solvent for the polyvinylidene fluoride resin, and a conductive carbon material, which sequentially includes the first, second, and third steps described below, and a method for producing the composite slurry and an electrode and a battery using the composite slurry. Patent Document 1 discloses a first step of mixing the active material and the polyvinylidene fluoride resin to produce a mixed powder, a second step of adding the mixed powder to a good solvent for the polyvinylidene fluoride resin to simultaneously dissolve the polyvinylidene fluoride resin and disperse the active material, and a third step of adding a conductive carbon material to the dispersion solution and kneading to produce a composite slurry.
[0005] Patent Document 2 discloses a nonaqueous secondary battery and a manufacturing method thereof, the battery comprising: a first step of obtaining a paste A containing an active material made of a lithium-containing transition metal oxide, a first binder A, and a dispersion medium; a second step of obtaining a paste B containing a conductive agent made of carbon black, a second binder B, and a dispersion medium; a third step of mixing paste A and paste B to obtain a positive electrode mixture paste C; a fourth step of applying the positive electrode mixture paste C to a core material of a positive electrode, rolling it, and drying it to obtain a positive electrode; and a fifth step of assembling a battery using the positive electrode, a negative electrode, and a nonaqueous electrolyte, wherein a contact angle θA of the nonaqueous electrolyte to binder A and a contact angle θB of the nonaqueous electrolyte to binder B satisfy formula (1): θB-θA≧15°.
[0006] Patent Document 3 discloses an electrode, a battery, and a battery pack which include an active material-containing layer containing active material particles, a binder covering the surfaces of the active material particles at a coverage rate of 80% or more and less than 99%, and a conductive agent, in which, in an integrated pore volume distribution of the active material-containing layer measured by mercury intrusion porosimetry, the pore volume of a region having a pore diameter of 0.1 μm or less is 0.035 mL / g or more and 0.050 mL / g or less, and the amount of carbon dioxide generated from the active material-containing layer measured by pyrolysis gas chromatography from 150° C. to 600° C. is 9 mL / g or more and 10 mL / g or less. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2013-196804 A [Patent Document 2] JP 2003-163006 A [Patent Document 3] International Publication No. 2020 / 194385 Summary of the Invention [Problem to be solved by the invention]
[0008] It is known that a positive electrode using hollow-structured positive electrode active material particles as a positive electrode active material can obtain a high output even when the SOC (State of Charge) of the battery is low. The hollow-structured positive electrode active material particles have a shell and a hollow portion formed inside the shell. Furthermore, such positive electrode active material particles may have a through hole that communicates the outside of the shell with the hollow portion.
[0009] When manufacturing a positive electrode, a process of mixing positive electrode active material particles with a conductive material is performed. When a conductive material having a diameter smaller than the diameter of the through-holes provided in the positive electrode active material particles is used, the conductive material may enter the hollow portion from the outside of the shell through the through-holes. In a positive electrode in which the conductive material has entered the hollow portion of the positive electrode active material particles, the amount of conductive material disposed outside the shell is reduced, so that the conductive path between the positive electrode active material particles formed by the conductive material may be insufficient. As a result, there is a problem that even if a conductive material is used, it may not be possible to suitably suppress an increase in the electronic resistance of the positive electrode.
[0010] The present disclosure has been made to solve such problems, and aims to provide a positive electrode for a lithium ion secondary battery in which an increase in electronic resistance is suitably suppressed by forming a good conductive path, and a method for manufacturing a positive electrode for a lithium ion secondary battery. [Means for solving the problem]
[0011] A positive electrode for a lithium ion secondary battery according to one embodiment includes a positive electrode current collector and a positive electrode composite layer formed on the positive electrode current collector. The positive electrode composite layer includes positive electrode active material particles having a hollow structure, the positive electrode active material particles having a shell portion made of a lithium transition metal oxide, a hollow portion formed inside the shell portion, and through holes connecting the outside of the shell portion to the hollow portion, a first conductive material having an average diameter larger than the average diameter of the through holes and arranged so as to block the through holes, and a second conductive material having an average diameter smaller than the average diameter of the through holes and arranged outside the shell portion.
[0012] In addition, a manufacturing method of a positive electrode for a lithium ion secondary battery according to one embodiment includes a first mixing step of obtaining a first mixture by mixing positive electrode active material particles having a hollow structure, the positive electrode active material particles having a shell portion made of a lithium transition metal oxide, a hollow portion formed inside the shell portion, and through holes connecting the outside of the shell portion to the hollow portion, and a first conductive material having an average diameter larger than the average diameter of the through holes; a second mixing step of obtaining a second mixture by mixing the first mixture with a second conductive material having an average diameter smaller than the average diameter of the through holes; a coating step of coating the second mixture on a positive electrode current collector; a drying step of drying the coated second mixture; and a pressing step of pressing the dried second mixture. Effect of the Invention
[0013] The present disclosure can provide a positive electrode for a lithium ion secondary battery in which an increase in electronic resistance is suitably suppressed by forming a good conductive path, and a method for producing a positive electrode for a lithium ion secondary battery. [Brief description of the drawings]
[0014] [Figure 1] FIG. 2 is a cross-sectional view showing a schematic example of a positive electrode plate according to the first embodiment. [Diagram 2] FIG. 2 is a diagram showing a schematic appearance of positive electrode active material particles contained in the positive electrode plate shown in FIG. [Diagram 3] 4 is a flowchart showing a method for manufacturing a positive electrode plate according to the first embodiment. [Figure 4] FIG. 2 is a diagram showing a schematic appearance of positive electrode active material particles contained in the positive electrode plate of Example 1. [Diagram 5] FIG. 2 is a diagram showing a schematic diagram of the results of particle size distribution measurement of carbon nanotubes. [Figure 6] FIG. 4 is a diagram showing a schematic appearance of positive electrode active material particles contained in the positive electrode plate of Example 2. [Figure 7] FIG. 4 is a diagram showing a cross section of a positive electrode active material particle included in a positive electrode plate of a comparative example. [Figure 8] FIG. 2 is a diagram showing a schematic appearance of positive electrode active material particles contained in a positive electrode plate of a reference example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] First embodiment Hereinafter, an embodiment of the present disclosure will be described with reference to the drawings. However, the present disclosure is not limited to the following embodiment. In addition, in order to clarify the description, the following description and drawings are appropriately simplified. In the following description, the same or equivalent elements are given the same reference numerals, and duplicate descriptions are omitted.
[0016] An example of a positive electrode plate 1 which is a positive electrode for a lithium ion secondary battery according to this embodiment will be described with reference to Fig. 1. Fig. 1 is a schematic diagram showing an example of a positive electrode plate according to the first embodiment.
[0017] The positive electrode plate 1 shown in FIG. 1 is used in a lithium ion secondary battery. The lithium ion secondary battery is configured by, for example, housing an electrode body having a positive electrode plate 1 and a negative electrode plate with a separator therebetween, and an electrolyte in a battery case. The lithium ion secondary battery is a battery that performs charging and discharging by conducting lithium ions, which are charge carriers, through the electrolyte between the positive electrode (positive electrode plate 1) and the negative electrode (negative electrode plate) during an electrochemical reaction. Such lithium ion secondary batteries are used as power sources for driving vehicles such as electric vehicles (EVs), hybrid vehicles (HVs), and plug-in hybrid vehicles (PHEVs).
[0018] As shown in FIG. 1, the positive electrode plate 1 has a positive electrode current collector 10 and a positive electrode composite layer 20 formed on the positive electrode current collector 10. The positive electrode current collector 10 is made of a conductive material made of a metal having good electrical conductivity, for example. As the conductive material, for example, a material containing aluminum or a material containing an aluminum alloy can be used. The configuration of the positive electrode current collector 10 is not limited to this.
[0019] The positive electrode mixture layer 20 includes a positive electrode active material that absorbs and releases lithium ions. The positive electrode active material contains a lithium transition metal oxide having a layered crystal structure. The lithium transition metal oxide contains one or more predetermined transition metal elements in addition to Li (lithium). The transition metal element contained in the lithium transition metal oxide is preferably at least one of Ni, Co, and Mn. A suitable example of the lithium transition metal oxide is a lithium transition metal oxide that contains all of Ni, Co, and Mn.
[0020] The positive electrode active material may additionally contain one or more elements in addition to the transition metal element (i.e., at least one of Ni, Co, and Mn). The additional element may include any element belonging to Group 1 (alkali metals such as sodium), Group 2 (alkaline earth metals such as magnesium and calcium), Group 4 (transition metals such as titanium and zirconium), Group 6 (transition metals such as chromium and tungsten), Group 8 (transition metals such as iron), Group 13 (metalloid element boron or metals such as aluminum), and Group 17 (halogens such as fluorine) of the periodic table.
[0021] In a preferred embodiment, the positive electrode active material may have a composition (average composition) represented by the following general formula (1). Li1+ x Ni y Co z Mn (1-y-z) MA α MB β O2…Equation (1)
[0022] In the above formula (1), x can be a real number satisfying 0 ≦ x ≦ 0.2. y can be a real number satisfying 0.1 < y < 0.6. z can be a real number satisfying 0.1 < z < 0.6. MA is at least one metal element selected from W, Cr, and Mo, and α is a real number satisfying 0 < α ≦ 0.01 (typically 0.0005 ≦ α ≦ 0.01, for example 0.001 ≦ α ≦ 0.01). MB is one or more elements selected from the group consisting of Zr, Mg, Ca, Na, Fe, Zn, Si, Sn, Al, B, and F, and β can be a real number satisfying 0 ≦ β ≦ 0.01. β may be substantially 0 (that is, an oxide substantially free of MB). In the chemical formula indicating the layered lithium transition metal oxide, for the sake of convenience, the composition ratio of O (oxygen) is shown as 2, but this numerical value should not be strictly interpreted and some composition variations (typically included in the range of 1.95 or more and 2.05 or less) can be tolerated.
[0023] The positive electrode active material particles 30 constituting the positive electrode active material have a particle form with a hollow structure. The positive electrode active material particles 30 can typically be substantially spherical, slightly distorted spherical, etc. The positive electrode active material particles 30 have a shell portion 31 made of a lithium transition metal oxide, a hollow portion 32 formed inside the shell portion 31, and a through-hole 33 that communicates the outside of the shell portion 31 and the hollow portion 32.
[0024] The shell portion 31 is formed by, for example, a plurality of primary particles 34. Specifically, the shell portion 31 is formed in a substantially spherical shell shape by the aggregation of a plurality of primary particles 34 of a lithium transition metal oxide. That is, the positive electrode active material particles 30 are secondary particles in which the primary particles 34 are aggregated. Here, the primary particles 34 refer to particles that can be considered as unit particles (ultimate particles) judged from the geometric form in appearance. In the positive electrode active material particles 30 disclosed herein, the primary particles 34 are typically aggregates of crystallites of a lithium transition metal oxide. The shape of the positive electrode active material particles 30 can be observed by an SEM (Scanning Electron Microscope) image. The hollow portion 32 is a space larger than the gaps existing between adjacent secondary particles.
[0025] The average particle size of the primary particles 34 is preferably, for example, 0.5 μm or more and 3.0 μm or less. If the average particle size of the primary particles 34 is too small, the capacity retention of the battery may tend to decrease. From this viewpoint, the average particle size of the primary particles 34 is preferably 0.2 μm or more, more preferably 0.3 μm or more, and even more preferably 0.4 μm or more. On the other hand, if the average particle size of the primary particles 34 is too large, the distance from the surface to the inside of the crystal (the diffusion distance of lithium ions) becomes long, so that the ion diffusion into the inside of the crystal becomes slow, and the output characteristics of the battery (particularly, the output characteristics in the low SOC range) tend to be low. From this viewpoint, the average particle size of the primary particles 34 is preferably 0.8 μm or less. In a preferred embodiment, the average particle size of the primary particles 34 is 0.2 μm or more and 0.8 μm or less.
[0026] In the present embodiment, the "average particle size" refers to the median diameter (D 50 The particle size can be determined as the 50% volume average particle size. For particle sizes of approximately 1 μm or more, it can be determined by the laser diffraction / light scattering method. For particle sizes of approximately 1 μm or less, it can be determined by the dynamic light scattering (DLS) method.
[0027] The average particle size of the positive electrode active material particles 30 is, for example, preferably about 2 μm or more, and more preferably 3 μm or more. If the average particle size of the positive electrode active material particles 30 is too small, the volume of the hollow portion 32 will also be small, and the amount of electrolyte stored in the hollow portion 32 will also be small. From the viewpoint of productivity, the average particle size of the positive electrode active material particles 30 is preferably 25 μm or less, and more preferably 15 μm or less. In a preferred embodiment, the average particle size of the positive electrode active material particles 30 is 3 μm or more and 10 μm or less.
[0028] In a preferred embodiment, the shell 31 has a configuration in which the primary particles 34 are connected in a ring shape (bead-like shape). The primary particles 34 may be a single layer or multiple layers in the thickness direction of the shell 31. In a preferred embodiment, the positive electrode active material particle 30 is configured in a configuration in which the primary particles 34 are substantially connected in a single layer over the entire shell 31. When the shell 31 has a multi-layer structure, the number of stacked primary particles 34 is preferably about 5 or less (e.g., 2 to 5), and more preferably about 3 or less (e.g., 2 to 3). The positive electrode active material particle 30 shown in FIG. 1 shows an example of the configuration, and the number of layers of the shell 31, the shape of the hollow portion 32, the ratio of the thickness of the shell 31 to the width of the hollow portion 32, the number and size of the through holes 33, etc. are not limited to those of the positive electrode active material particle 30 shown in FIG. 1.
[0029] Moreover, the shell portion 31 is sintered densely at least to the extent that it does not allow the electrolyte to pass through the portions other than the through holes 33. According to the positive electrode active material particle 30 having this structure, the portions where the electrolyte can flow between the outside of the shell portion 31 and the hollow portion 32 are limited to the portions where the through holes 33 are present.
[0030] The thickness of shell portion 31 is preferably 3.0 μm or less, more preferably 2.5 μm or less, and further preferably 2.0 μm or less. The smaller the thickness of shell portion 31, the more easily lithium ions are released from the inside of shell portion 31 (the central part of the thickness) during charging, and the more easily lithium ions are absorbed into shell portion 31 during discharging.
[0031] The lower limit of the thickness of the shell 31 is not particularly limited, but is usually preferably about 0.1 μm or more. By making the thickness of the shell 31 0.1 μm or more, it is possible to maintain high durability against stress that may be applied during the manufacture or use of the battery, and against the expansion and contraction of the positive electrode active material accompanying charging and discharging. From the viewpoint of achieving both the internal resistance reduction effect and durability, the thickness of the shell 31 is preferably about 0.1 μm or more and 2.2 μm or less, more preferably 0.2 μm or more and 2.0 μm or less, and particularly preferably 0.5 μm or more and 1.5 μm or less.
[0032] The through holes 33 are formed to penetrate the shell portion 31. The through holes 33 allow the electrolyte to pass between the hollow portion 32 and the outside of the shell portion 31. The through holes 33 are formed by gaps provided between a plurality of primary particles 34 that constitute the shell portion 31. By providing the through holes 33 in the shell portion 31, the electrolyte from the outside can easily flow into the hollow portion 32 through the through holes 33, and the electrolyte in the hollow portion 32 can easily flow out to the outside through the through holes 33. As a result, the electrolyte in the hollow portion 32 is appropriately replaced.
[0033] In addition, since the electrolyte is stored in hollow portion 32, it is difficult for electrolyte drying up, such as a shortage of electrolyte, to occur in positive electrode mixture layer 20. Since a lithium-ion secondary battery performs charging and discharging by the movement of lithium ions, by facilitating the movement of electrolyte between hollow portion 32 and the outside of shell portion 31, primary particles 34 facing hollow portion 32 can be more actively utilized for charging and discharging.
[0034] The internal resistance of a lithium ion secondary battery is composed of a number of resistance components, such as the charge transfer resistance at the interface between the active material and the electrolyte, the diffusion transfer resistance of lithium ions in the positive electrode active material, the solution resistance of the electrolyte, etc. In the case of the hollow structured positive electrode active material particles 30, the number and diameter of the through holes 33 also affect the diffusion of lithium ions and are therefore considered to contribute to the internal resistance of the lithium ion secondary battery.
[0035] The number of through holes 33 provided in the positive electrode active material particle 30 is preferably about 1 to 10 (for example, 1 to 5) on average per particle of the positive electrode active material particle 30. If the average number of through holes 33 is too large, it may be difficult to maintain a hollow shape. Furthermore, the greater the average number of through holes, the easier it is for the electrolyte to pass back and forth, but increasing the average number of through holes 33 reduces the amount of positive electrode active material per unit volume, resulting in a decrease in energy density. For this reason, it is preferable to keep the number of through holes 33 to a minimum.
[0036] The average diameter of the through holes 33 provided in the positive electrode active material particles 30 is preferably, for example, 10 nm or more and 100 nm or less. When the average diameter of the through holes 33 is 10 nm or more, the through holes 33 can function more effectively as a flow path for the electrolyte. When the average diameter of the through holes 33 is larger than 100 nm, the porosity of the shell portion 31 as a whole increases, and the strength of the shell portion 31 may decrease. The average diameter of the through holes 33 can be calculated as the average value of the diameters of the narrowest parts of about 10 through holes 33 arbitrarily selected from an SEM image obtained by observing the cross section of the positive electrode active material particles 30.
[0037] The first conductive material 41 and the second conductive material 42 are materials that form a conductive path in the positive electrode mixture layer 20. The first conductive material 41 has an average diameter (average particle size) larger than the average diameter of the through holes 33, and is arranged so as to block the through holes 33. When the positive electrode plate 1 is manufactured, the first conductive material 41 blocks the through holes 33, thereby suppressing the second conductive material 42 from entering the hollow portions 32. In addition, the first conductive material 41 is attached to the surfaces of the positive electrode active material particles 30 so as to block the through holes 33, thereby electrically connecting the positive electrode active material particles 30 and the second conductive material 42.
[0038] The average particle size of first conductive material 41 is preferably, for example, 100 nm or more and 1 μm or less. If the average particle size of first conductive material 41 is 1 μm or more, the efficiency of forming a conductive path in positive electrode mixture layer 20 may decrease. On the other hand, if the average particle size of first conductive material 41 is 100 nm or less, first conductive material 41 may pass through through hole 33 and enter hollow portion 32.
[0039] The first conductive material 41 is made of a carbon material having electrical conductivity. Examples of the carbon material constituting the first conductive material 41 include carbon black such as acetylene black (AB), ketzen black, and furnace black, particulate carbon materials such as graphite, and fibrous carbon materials such as vapor grown carbon fiber (VGCF), carbon nanotubes (CNT), and carbon nanofibers (CNF). As the first conductive material 41, these carbon materials may be used alone or in combination of two or more kinds.
[0040] The carbon material constituting the first conductive material 41 may be primary particles, or may be agglomerated particles (secondary particles) formed by agglomerating primary particles. In a preferred embodiment, the first conductive material 41 contains agglomerated particles of at least one of a particulate carbon material and a fibrous carbon material. This allows the first conductive material 41 to reliably block the through holes 33, thereby further preventing the second conductive material 42 from entering the hollow portion 32.
[0041] In order to set the average particle size of the first conductive material 41 within the above range, the average particle size of the primary particles of the particulate carbon material is preferably, for example, 10 nm or more and 100 nm or less. The shape of the particulate carbon material is not particularly limited as long as it is particulate, and examples thereof include a spherical shape and an elliptical shape. In order to exhibit high conductivity and form a good conductive path, the particulate carbon material is preferably AB, and the fibrous carbon material is preferably CNT.
[0042] Whether or not the first conductive material 41 contains agglomerated particles can be determined from the particle size distribution spectrum obtained by measuring a measurement sample in which the first conductive material 41 is dispersed in an appropriate solvent. For example, a particle size distribution spectrum including two or more peaks indicates that the material contains agglomerated particles. On the other hand, a particle size distribution spectrum including one peak indicates that the material does not contain agglomerated particles.
[0043] The second conductive material 42 has an average diameter smaller than the average diameter of the through-holes 33, and is disposed outside the shell portion 31. The second conductive material 42 forms a conductive path between the positive electrode active material particles 30, and also forms a conductive path between the positive electrode active material particles 30 and the positive electrode current collector 10. In addition, the second conductive material 42 contacts and is electrically connected to the first conductive material 41 disposed so as to block the through-holes 33.
[0044] The second conductive material 42 is made of a carbon material having electrical conductivity. As the second conductive material 42, the carbon materials exemplified in the first conductive material 41 may be used alone or in combination of two or more kinds. The second conductive material 42 preferably contains a fibrous carbon material because a conductive path between the positive electrode active material particles 30 can be efficiently formed with a smaller amount of carbon material than with a particulate carbon material. By disposing the fibrous carbon material as the second conductive material 42 between the positive electrode active material particles 30, a dense conductive network is formed between the positive electrode active material particles 30 and between the positive electrode mixture layer 20 and the positive electrode current collector 10. As a result, electrons are efficiently transferred between the positive electrode active material particles 30 and between the positive electrode mixture layer 20 and the positive electrode current collector 10, so that the electrical conductivity of the positive electrode mixture layer 20 is improved. As a result, an increase in the electronic resistance of the positive electrode plate 1 can be suppressed.
[0045] Furthermore, by using a fibrous carbon material as the second conductive material 42, the proportion of the second conductive material 42 in the positive electrode mixture layer 20 can be reduced. This allows the proportion of the positive electrode active material in the positive electrode mixture layer 20 to be increased, resulting in a positive electrode plate 1 with a higher energy density. CNTs are preferable as the second conductive material 42 because they exhibit high conductivity and form good conductive paths. CNTs can be prepared by a manufacturing method such as chemical vapor deposition (CVD), arc discharge, or laser evaporation. Commercially available products may also be used.
[0046] The average diameter of the second conductive material 42 is preferably, for example, 5 nm or more and 30 nm or less. If the average diameter of the second conductive material 42 is 30 nm or more, the efficiency of forming a conductive path in the positive electrode mixture layer 20 may decrease. On the other hand, if the average diameter of the second conductive material 42 is 5 nm or less, the mechanical strength and dispersibility may decrease. The average diameter of the second conductive material 42 can be obtained as the average value of the outer diameters of 10 second conductive materials 42 arbitrarily selected from an SEM image obtained by observing the second conductive material 42 with an SEM.
[0047] The length of the fibrous carbon material is not particularly limited. The longer the fibrous carbon material is, the more efficiently it can form a conductive path in the positive electrode composite layer 20. On the other hand, the longer the fibrous carbon material is, the lower the dispersibility becomes. From these viewpoints, the average length of the second conductive material 42 is preferably, for example, 1 μm or more and 10 μm or less. The average length of the second conductive material 42 can be measured, for example, based on an SEM image of the second conductive material 42. For example, the average diameter of the second conductive material 42 can be calculated as the average value of the lengths of 10 second conductive materials 42 arbitrarily selected from an SEM image obtained by observing the second conductive material 42 with an SEM.
[0048] Here, Fig. 2 is a diagram showing a schematic appearance of the positive electrode active material particles contained in the positive electrode plate shown in Fig. 1. In a preferred embodiment, the positive electrode plate 1 satisfies the following formula (a) when the average particle size of the primary particles 34 is D1, the average diameter of the through holes 33 is D2, and the average particle size of the first conductive material 41 is D3. D3≧D1+D2...Formula (a)
[0049] Since the average particle size of the first conductive material 41 is equal to or greater than the sum of the average particle size of the primary particles 34 and the average diameter of the through holes 33, the first conductive material 41 can reliably block the through holes 33, thereby further preventing the second conductive material 42 from penetrating the hollow portions 32.
[0050] Returning to Fig. 1, the positive electrode mixture layer 20 preferably contains a binder in addition to the positive electrode active material particles 30, the first conductive material 41, and the second conductive material 42. As the binder, a polymer that can be dissolved or dispersed in the solvent used can be used. Examples of the binder include polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyacrylic acid, polyacrylate, etc.
[0051] The positive electrode mixture layer 20 preferably contains a dispersant. Examples of the dispersant include polyvinyl alcohol (PVA), polyvinyl butyral (PVB), polyvinylpyrrolidone (PVP), polyacrylate, polymethacrylate, polyoxyethylene alkyl ether, polyalkylene polyamine, and benzimidazole. The positive electrode mixture layer 20 may further contain other additives.
[0052] The proportion of the positive electrode active material in the entire positive electrode active material layer is preferably 50 mass% or more (typically 90 to 99 mass%), and preferably 95 to 99 mass%. The proportion of the binder in the entire positive electrode active material layer is, for example, preferably 5 mass% or less, and preferably 1 mass% or less (for example, about 0.5 to 1 mass%, for example 0.8 mass%). The total proportion of the first conductive material 41 and the second conductive material 42 in the entire positive electrode active material layer is preferably 10 mass% or less, and preferably 9 mass% or less (for example, about 8 mass%). If the proportion of the first conductive material 41 and the second conductive material 42 is too high, the mass per unit volume of the positive electrode active material decreases, and the desired energy density may not be obtained. On the other hand, if the proportion of the conductive material is too low, the conductivity of the positive electrode active material layer decreases, and the electronic resistance of the positive electrode plate 1 may increase.
[0053] Furthermore, the mass ratio of the first conductive material 41 to the second conductive material 42 (mass of the first conductive material 41 / mass of the second conductive material 42) is preferably, for example, 0.1 or more and 0.5 or less. If the ratio of the first conductive material 41 to the second conductive material 42 is 0.5 or more, the conductive paths between the positive electrode active material particles 30 formed by the second conductive material 42 may be insufficient. On the other hand, if the ratio of the first conductive material 41 to the second conductive material 42 is 0.1 or less, it may be difficult for the first conductive material 41 to block the through holes 33.
[0054] Next, a method for manufacturing the positive electrode plate 1 according to this embodiment will be described with reference to Fig. 3. Fig. 3 is a flowchart showing the method for manufacturing the positive electrode plate according to embodiment 1. As shown in Fig. 3, the method for manufacturing the positive electrode plate 1 according to this embodiment includes the following steps S1 to S5.
[0055] Step S1 is a first mixing step in which a hollow-structured positive electrode active material particle 30 having a shell 31 made of a lithium transition metal oxide, a hollow portion 32 formed inside the shell 31, and a through hole 33 communicating the outside of the shell 31 with the hollow portion 32 is mixed with a first conductive material 41 having an average diameter larger than the average diameter of the through hole 33 to obtain a first mixture. Step S2 is a second mixing step in which a second mixture is obtained by mixing the first mixture with a second conductive material 42 having an average diameter smaller than the average diameter of the through hole 33. Step S3 is a coating step in which the second mixture is coated on the positive electrode current collector 10. Step S4 is a drying step in which the coated second mixture is dried. Step S5 is a pressing step in which the dried second mixture is pressed.
[0056] Each of the above steps will be described in more detail. First, in the first mixing step (step S1), the positive electrode active material particles 30 and the first conductive material 41 are prepared. First, the steps of producing the positive electrode active material particles 30 include, for example, a raw hydroxide generating step, a mixing step, and a baking step. In the raw hydroxide generating step, ammonium ions (NH4 + ) to precipitate particles of a transition metal hydroxide from the aqueous solution, where the aqueous solution contains at least one transition metal element that constitutes the lithium transition metal oxide.
[0057] The raw hydroxide production process preferably includes a nucleation stage in which a transition metal hydroxide is precipitated from an aqueous solution, and a particle growth stage in which transition metal hydroxide particles are grown in a state in which the pH of the aqueous solution is reduced from that in the nucleation stage. In the particle growth stage, the structure of the shell 31 can be changed by adjusting the precipitation rate of the transition metal hydroxide by changing the pH and ammonium ion concentration. By lowering the ammonium ion concentration in the reaction solution and increasing the precipitation rate, it becomes easier to produce hollow-structured positive electrode active material particles 30 having through holes 33. In addition, the particle porosity and the like can also be adjusted by adjusting the particle growth time.
[0058] In the mixing step, the transition metal hydroxide particles produced in the raw hydroxide production step are separated from the reaction solution, washed, filtered, and dried. The transition metal hydroxide thus obtained is mixed with a lithium compound to prepare a mixture for forming the shell portion. The transition metal hydroxide and the lithium compound are preferably mixed as uniformly as possible at a predetermined ratio. In the mixing step, the lithium compound and the transition metal hydroxide particles are typically mixed in a ratio corresponding to the composition of the target positive electrode active material particles 30.
[0059] The firing step is a step of firing the shell-forming mixture to obtain the positive electrode active material particles 30. The firing step is performed, for example, in an oxidizing atmosphere (for example, in an air atmosphere). The firing temperature is, for example, 700°C or higher and 1100°C or lower. The firing step may include a plurality of steps in which firing is performed in different temperature ranges. After firing, it is preferable to crush the fired product and classify it to adjust the average particle size, if necessary.
[0060] In this step, a sintering reaction of the primary particles 34 of the lithium transition metal oxide is allowed to proceed. As a result, the primary particles 34 are sintered together to form a generally spherical shell portion 31 in which the primary particles 34 are connected, and a hollow portion 32 is formed inside the shell portion 31. Furthermore, when the crystals grow during sintering, a through hole 33 that connects the outside of the shell portion 31 to the hollow portion 32 is formed in a part of the shell portion 31.
[0061] In the first mixing step, the positive electrode active material particles 30 and the first conductive material 41 are mixed to obtain a first mixture. The first mixture may contain a binder. In this embodiment, the positive electrode active material particles 30, the first conductive material 41, the binder, and the solvent are kneaded using an appropriate kneading device to obtain a first mixture containing the positive electrode active material particles 30, the first conductive material 41, the binder, and the solvent. Preferably, the first mixture is obtained by adding the positive electrode active material particles 30 and the first conductive material 41 to a binder solution in which the binder is dispersed or dissolved in a solvent, and kneading the mixture.
[0062] Here, the first conductive material 41 needs to be arranged so as to block the through holes 33. During kneading in the first mixing step, the first conductive material 41 is fixed to the primary particles 34 arranged around the through holes 33 by at least one of the intermolecular forces between the first conductive material 41, the binding force of the first conductive material 41 itself, and the action of the dispersant. In this way, the through holes 33 are blocked by the first conductive material 41 in the first mixture.
[0063] The solvent may be selected appropriately according to the binder used as long as it can dissolve or disperse the binder uniformly. Examples of the solvent that can be used include non-aqueous solvents such as N-methyl-2-pyrrolidone (NMP), methyl ethyl ketone (MEK), dimethylformamide (DMF), and toluene, mixed solvents combining non-aqueous solvents, and aqueous solvents such as water and mixed solvents mainly composed of water. For the kneading in the first mixing step, kneading devices such as a planetary mixer, a disperser, a ball mill, an extrusion kneader, and a mixer can be used.
[0064] In the second mixing step (step S2), the second conductive material 42 is prepared. In the second mixing step, the first mixture obtained in the first mixing step and the second conductive material 42 are mixed to obtain a second mixture. The second mixture may contain a dispersant for dispersing the second conductive material 42. In this embodiment, the first mixture, the second conductive material 42, and the dispersant are kneaded using an appropriate kneading device to obtain a second mixture containing the positive electrode active material particles 30, the first conductive material 41, the second conductive material 42, a binder, a dispersant, and a solvent. Preferably, the second mixture is obtained by adding a paste-like or slurry-like conductive material composition containing the second conductive material 42, a dispersant, and a solvent to the first mixture and kneading them.
[0065] The solvent may be any solvent that disperses the second conductive material 42 in the second mixture, and may be, for example, the same solvent as in the first mixing step or a different solvent than that in the first mixing step. For kneading in the second mixing step, for example, the same kneading device as in the first mixing step or a different kneading device than that in the first mixing step may be used. From the viewpoint of productivity, it is preferable to use the same solvent and the same kneading device in the first mixing step and the second mixing step.
[0066] Here, in the first mixing step, the through holes 33 are blocked with the first conductive material 41. Therefore, in the second mixing step, the second conductive material 42 is disposed outside the shell portion 31 in the second mixture.
[0067] The positive electrode active material particles 30 are preferably 80% by mass or more and 98% by mass or less with respect to 100% by mass of the total amount of solids in the second mixture. The first conductive material 41 is preferably 0.5% by mass or more and 3% by mass or less with respect to 100% by mass of the total amount of solids in the second mixture. The binder is preferably 0.5% by mass or more and 3% by mass or less with respect to 100% by mass of the total amount of solids in the second mixture. The dispersant is preferably 0.01% by mass or more and 1% by mass or less with respect to 100% by mass of the total amount of solids in the second mixture.
[0068] The viscosity of the second mixture is preferably, for example, 1000 Pa·s or more and 20000 Pa·s or less. If the viscosity of the second mixture is 20000 Pa·s or more or 1000 Pa·s or less, the coatability of the second mixture may decrease.
[0069] In the coating step (step S3), the second mixture can be applied onto the positive electrode current collector 10 using a coating device such as a die coater, a comma coater, a knife coater, or a gravure coater.
[0070] In the drying step (step S4), the second mixture applied onto the positive electrode current collector 10 may be dried naturally or by heating. When the second mixture is dried by heating, a suitable drying device such as a hot air dryer or an infrared heating device can be used. The drying step can remove the solvent contained in the second mixture.
[0071] In the pressing step (step S5), a pressing device such as a roll press can be used for pressing (compressing) the dried second mixture. The density and thickness of positive electrode mixture layer 20 can be adjusted by the pressing step.
[0072] The amount of positive electrode mixture layer 20 applied per unit area on positive electrode current collector 10 is not particularly limited, but from the viewpoint of ensuring a sufficient conductive path, it is set to 3 mg / cm 2 per one side of positive electrode current collector 10. 2 More than 5 mg / cm is preferable. 2 More preferably, 6 mg / cm or more is preferable. 2 The coating amount is the coating amount calculated as the solid content of the composition for forming a positive electrode mixture layer.
[0073] The coating amount per one side of the positive electrode current collector 10 is 45 mg / cm 2 Less than 28 mg / cm is preferred. 2 Less than 15 mg / cm is more preferable, and particularly 15 mg / cm 2 The density of the positive electrode mixture layer 20 is not particularly limited, but is preferably 1.0 g / cm 3 More than 3.8g / cm3 It is preferable that the density is 1.5 g / cm or less. 3 More than 3.0g / cm 3 Less than 1.8 g / cm is more preferable. 3 More than 2.4g / cm 3 It is preferable that:
[0074] By the above steps, the positive electrode plate 1 shown in FIG. 1 can be manufactured.
[0075] Next, Examples 1 and 2, a Comparative Example, and a Reference Example will be described with reference to Figures 4 to 8. Note that the present disclosure is not limited to the Examples.
[0076] Example 1 The positive electrode plate 1 of Example 1 was manufactured according to the flow shown in FIG. 3. FIG. 4 is a diagram showing a schematic appearance of the positive electrode active material particles contained in the positive electrode plate of Example 1. First, in the first mixing step, the positive electrode active material particles 30, which are secondary particles formed by aggregation of the primary particles 34, the aggregated particles 41a of AB as the first conductive material 41, PVDF as the binder, and NMP as the solvent were prepared. In the positive electrode active material particles 30, the primary particles 34 had an average particle size of 0.3 μm, the through holes 33 had an average diameter of 100 μm, and the secondary particles had an average particle size of 4 μm. The aggregated particles 41a of AB were formed by aggregation of primary particles having an average particle size of 40 to 60 μm, and had an average particle size of 2 to 4 μm.
[0077] In the first mixing step, the positive electrode active material particles 30 and the aggregated particles 41a of AB were added to a binder solution in which PVDF was dissolved in NMP, and the mixture was kneaded using a kneading device. As a result, a paste-like first mixture was obtained. In the first mixing step, the positive electrode active material particles 30 were mixed at a mass ratio of 95 mass %, 3 mass % of AB, and 2 mass % of PVDF.
[0078] Next, in the second mixing step, CNTs 42a and a dispersant were prepared as the second conductive material 42. The CNTs 42a had an average diameter of 15 nm and a fiber length of 500 to 2000 nm. In the second mixing step, a paste-like conductive material composition in which the CNTs 42a were dispersed in NMP containing a dispersant was added to the first mixture, and kneaded using a kneading device. As a result, a paste-like second mixture with a viscosity of 5000 Pa·s was obtained. In the second mixing step, the positive electrode active material particles 30 were mixed in a mass ratio of 93.5 mass %, AB 3 mass %, CNTs 42a 1 mass %, PVDF 2 mass %, and dispersant 0.5 mass %.
[0079] Next, in the coating step, the obtained second mixture is applied to one side of an aluminum foil (thickness 15 μm) serving as a positive electrode current collector 10 in a coating amount of 5 to 6 mg / cm2 per side. 2 In the drying step, the applied second mixture was dried under drying conditions of a drying temperature of 100 to 120° C. and a drying time of 20 to 40 minutes, and then in the pressing step, the density of the positive electrode mixture layer 20 formed on the positive electrode current collector 10 was adjusted to 2.5 to 3.0 g / cm 3 By pressing the positive electrode plate 1 according to the first embodiment, a positive electrode plate 1 was obtained.
[0080] Therefore, in Example 1, the average particle size of AB aggregated particles 41a is larger than the average diameter of through holes 33, and the average diameter of CNTs 42a is smaller than the average diameter of through holes 33. Moreover, Example 1 satisfies the above formula (a).
[0081] Then, when an SEM image of the positive electrode plate 1 of Example 1 was observed, as shown in Fig. 4, the positive electrode plate 1 of Example 1 had agglomerated particles 41a of AB arranged so as to block the through-holes 33 of the positive electrode active material particles 30, and CNTs 42a arranged in a dispersed state outside the shell portion 31. On the other hand, the penetration of the primary particles of AB, agglomerated particles 41a, and CNTs 42a into the hollow portion 32 was not confirmed. Furthermore, when the electronic resistance of the positive electrode plate 1 of Example 1 was measured with a resistance meter, it was 0.5 Ω cm 2 It was.
[0082] Example 2 6 is a diagram showing a schematic appearance of positive electrode active material particles contained in a positive electrode plate of Example 2. Positive electrode plate 1 of Example 2 was manufactured by the same method as in Example 1, except that aggregated particles 41b of CNTs were used as first conductive material 41. Aggregated particles 41b of CNTs had an average diameter of 15 nm and were aggregates of CNTs having fiber lengths of 500 to 2000 nm, and had an average particle diameter of 3 to 10 μm.
[0083] Therefore, in Example 2, the average particle size of CNT agglomerated particles 41b is larger than the average diameter of through holes 33, and the average diameter of CNTs 42a is smaller than the average diameter of through holes 33. Moreover, Example 2 satisfies the above formula (a).
[0084] Here, Fig. 5 is a diagram showing the results of particle size distribution measurement of carbon nanotubes. Fig. 5 shows two types of spectrum of particle size distribution measured by a particle size distribution measuring device using DLS method. The spectrum of the first conductive material 41 shown in the upper part of Fig. 5 contains two or more peaks, so it was determined that the first conductive material 41 contains aggregated particles 41b of CNT. The spectrum of the second conductive material 42 shown in the lower part of Fig. 5 contains one peak, so it was determined that the second conductive material 42 contains CNT 42a in a dispersed state that is not aggregated.
[0085] Then, when an SEM image of the positive electrode plate 1 of Example 2 was observed, as shown in Fig. 6, the positive electrode plate 1 of Example 2 had CNT agglomerated particles 41b arranged so as to block the through-holes 33 of the positive electrode active material particles 30, and CNTs 42a arranged in a dispersed state outside the shell portion 31. On the other hand, penetration of the CNT agglomerated particles 41b and CNTs 42a into the hollow portion 32 was not confirmed. Furthermore, when the electronic resistance of the positive electrode plate 1 of Example 2 was measured in the same manner as in Example 1, it was 0.5 Ω cm 2 It was.
[0086] (Comparative Example) FIG. 7 is a diagram showing a cross section of a positive electrode active material particle included in a positive electrode plate of a comparative example. A positive electrode active material particle 30 was used in which the average particle size of the primary particles 34 was 0.4 μm, the average diameter of the through holes 33 was 100 μm, and the average particle size of the secondary particles was 4.0 μm. In addition, as a conductive material instead of the first conductive material 41 and the second conductive material 42, CNTs 43 with an average diameter of 20 nm and a fiber length of 500 to 2000 nm were used. In the first mixing step, a conductive material composition in which CNTs 43 were dispersed in NMP containing a dispersant instead of the first conductive material 41 was mixed with other materials, and the second mixing step was omitted. A positive electrode plate of the comparative example was manufactured by the same method as in Example 1 except for these.
[0087] Therefore, in the comparative example, the average diameter of the CNTs 43 is smaller than the average diameter of the through holes 33, and does not satisfy the above formula (a).
[0088] Then, when an SEM image of the positive electrode plate of the comparative example was observed, it was found that the positive electrode plate of the comparative example had CNTs 43 arranged in the hollow portion 32 and CNTs 43 arranged in a dispersed state outside the shell portion 31, as shown in Fig. 7. Furthermore, when the electronic resistance of the positive electrode plate of the comparative example was measured in the same manner as in Example 1, it was found to be 1.5 Ω cm 2 It was.
[0089] (Reference example) 8 is a diagram showing a schematic diagram of the positive electrode active material particles contained in the positive electrode plate of the reference example. The positive electrode plate of the reference example was manufactured by the same method as the comparative example, except that the positive electrode active material particles 30 were used, in which the average particle size of the primary particles 34 was 0.3 μm, the average diameter of the through holes 33 was 15 nm, and the average particle size of the secondary particles was 4 μm.
[0090] Therefore, in the reference example, the average diameter of the CNTs 43 is larger than the average diameter of the through-holes 33, and does not satisfy the above formula (a).
[0091] Then, when an SEM image of the positive electrode plate of the reference example was observed, as shown in Fig. 8, the positive electrode plate of the reference example had CNTs 43 arranged in a dispersed state outside the shell portion 31. On the other hand, penetration of the CNTs 43 into the hollow portion 32 was not confirmed. Furthermore, when the electronic resistance of the positive electrode plate of the reference example was measured in the same manner as in Example 1, it was 0.4 Ω cm 2 It was.
[0092] In this way, Examples 1 and 2, in which the penetration of second conductive material 42 (CNTs 42a) into hollow portion 32 was suppressed by blocking through-hole 33 with first conductive material 41 (AB agglomerated particles 41a or CNT agglomerated particles 41b), had a reduced electronic resistance compared to the comparative example in which conductive material (CNTs 43) penetrated into hollow portion 32 through through-hole 33. Moreover, Examples 1 and 2 were able to achieve the same level of electronic resistance as the reference example in which good conductive paths were formed outside shell portion 31 by dispersed CNTs 43.
[0093] As described above, according to the manufacturing method of the positive electrode plate 1 and the positive electrode plate 1 of this embodiment, an excellent conductive path is formed, thereby making it possible to suitably suppress an increase in electronic resistance.
[0094] The present disclosure is not limited to the above-described embodiment, and can be modified as appropriate without departing from the spirit and scope of the present disclosure. [Explanation of symbols]
[0095] 1 Positive plate 10 Positive electrode current collector 20 Positive electrode mixture layer 30 Positive electrode active material particles 31 Shell part 32 Hollow part 33 Through hole 34 Primary particles 41 First conductive material 41a, 41b Agglomerated particles 42 Second conductive material 42a, 43 CNT
Claims
1. A positive electrode current collector; a positive electrode mixture layer formed on the positive electrode current collector; having The positive electrode mixture layer is a hollow structure positive electrode active material particle having a shell portion made of a lithium transition metal oxide, a hollow portion formed inside the shell portion, and a through hole connecting the outside of the shell portion to the hollow portion; a first conductive material having an average diameter larger than an average diameter of the through holes and disposed so as to close the through holes; a second conductive material having an average diameter smaller than an average diameter of the through holes and disposed outside the shell portion; A positive electrode for a lithium ion secondary battery comprising:
2. The shell portion is formed by a plurality of primary particles, 2. The positive electrode for a lithium ion secondary battery according to claim 1, wherein the following formula (a) is satisfied, where D1 is an average particle size of the primary particles, D2 is an average diameter of the through holes, and D3 is an average particle size of the first conductive material. D3≧D1+D2...Formula (a)
3. 2 . The positive electrode for a lithium ion secondary battery according to claim 1 , wherein the first conductive material includes aggregated particles of at least one of a particulate carbon material and a fibrous carbon material.
4. The positive electrode for a lithium ion secondary battery according to claim 1 , wherein the second conductive material includes a fibrous carbon material.
5. 4. The positive electrode for a lithium ion secondary battery according to claim 3, wherein the particulate carbon material is acetylene black.
6. 5. The positive electrode for a lithium ion secondary battery according to claim 3, wherein the fibrous carbon material is a carbon nanotube.
7. a first mixing step of obtaining a first mixture by mixing positive electrode active material particles having a hollow structure, the positive electrode active material particles having a shell portion made of a lithium transition metal oxide, a hollow portion formed inside the shell portion, and through holes communicating the outside of the shell portion with the hollow portion, and a first conductive material having an average diameter larger than the average diameter of the through holes; a second mixing step of mixing the first mixture with a second conductive material having an average diameter smaller than the average diameter of the through holes to obtain a second mixture; a coating step of coating the second mixture on a positive electrode current collector; a drying step of drying the applied second mixture; a pressing step of pressing the dried second mixture; The present invention relates to a method for producing a positive electrode for a lithium ion secondary battery.
Citation Information
Patent Citations
Nonaqueous secondary battery and its manufacturing method
JP2003163006A
Mixture slurry, manufacturing method thereof, electrode formed by mixture slurry, and battery
JP2013196804A
Electrode, battery and battery pack
WO2020194385A1
Cited By
Positive electrode sheet, battery, and electric device
WO2026158038A1
